Formulation And Evaluation Of Thymoquinone Loaded Nlc By Emulsion Evaporation Method - Dewangan, Akash; Kumar Omray, Lavakesh; Gupta, Naveen; Singh Rajput, Dharmendra; Kumar Pradhan, Dusmanta (Journal of Neonatal Surgery, 2025)
Nanoparticles based controlled drug release can also reduce the side effects of drugs. Benefits of nanoparticle drug delivery systems include minimised irritant reactions and improved penetration within the body due to their small size, allowing for intravenous and other delivery routes. Oral administration is the most convenient route among various routes of drug delivery as it offers high patient compliance. However, the poor aqueous solubility and poor enzymatic/metabolic stability of drugs are major limitations in successful oral drug delivery. There are several approaches to improve problems related to hydrophobic drugs. Among various approaches, nanotechnology-based drug delivery system has potential to overcome the challenges associated with the oral route of administration. Novel drug delivery systems are available in many areas of medicine. Nanoparticles (NPs) and other colloidal drug-delivery systems modify the kinetics, drug distribution in the body and release profile of an associated drug. Nanostructured lipid carriers (NLCs) have been promising formulation for effective oral drug delivery and opening new possibilities for NLCs in future pharmaceutical applications. Nanostructure lipid carriers (NLCs) are nanosized-based carrier systems which comprise solid lipid matrix combined with liquid lipids and surfactants. The aim of the paper is to explore the various advantages of formulation technology along with the characterization parameter of the NLCs.